Economies of scale and scope in French mutual funds - Dermine, Jean; Röller, Lars-Hendrik (Journal of Financial Intermediation, 1992)
This paper evaluates the economies of scale and scope in the French mutual funds (SICAV) industry. This segment of the financial sector offers the unique characteristic that some firms specialize, while others supply several products. The results suggest economies of scale and scope for small institutions and diseconomies for larger firms. An appropriate size for a diversified company is in the range of FF 2.9 billion.